Tratamentos de diferentes frações de Caesalpinia peltophoroides Benth em camundongos swiss : avaliação bioquímica, mutagênica e antimutagênica - Muller, Ana Paula (2016)
The Caesalpinia plants has several biological activies that arealready studied, as antimicrobial, antiviral, anti-inflammatory and antioxidant agent. The literature has little information about Caesalpinia peltophoroides species, popularly known as sibipiruna. Thus, the objective of this study is to evaluate the mutagenic and antimutagenic effects through the micronucleus test (MN) and biochemical (serum biomarkers) of treatment of flowers and leaves of C. peltophoroides using methanolic and ethyl acetate fractions. For micronucleus test, we used Swiss mice that were divided into 10 groups (n = 6) which received 150 mg/Kg of ethyl acetate fraction of flowers (AFL) or leaves (AFO), or methanolic fraction flower (MFL) or leaves (MFO) orally for 15 consecutive days. On the last day of treatment the negative control (group 1 - S) and four treatment groups: 7 (MFL), 8 (MFO), 9 (AFL) and 10 (AFO) received 0.9% NaCl solution to 0.1mL/10g. The positive control (group 2 - CPA) and groups 3 (MFL) 4 (MFO), 5 (AFL) and 6 (AFO) received 25 mg/Kg of cyclophosphamide (CPA). After 24 hours from the 15th day of treatment, the death of the animals was performed, collecting serum biochemical tests and bone marrow blood for evaluation of micronucleated polychromatic erythrocytes (MNPCEs). The frequency of micronucleus compared to the positive control group was 60.1% for the ethyl acetate fraction of flower, 55% for methanolic fraction of the leaf, 51.7% for the ethyl acetate fraction of leaves and 48.3% for methanolic fraction of flowers. There was a decreasing in HDL levels in groups treated with plants, without the interference of the CPA, and also with positive control group (CPA). There were no differences in serum creatinine, triglycerides, VLDL lipoproteins and AST activity. On the other hand, the ethyl acetate fraction of flowers (AFL) increased the ALT activity, whereas the leaves (AFO) decreased. The ethyl acetate fractions associated with CPA significantly altered the biochemical profile, once it decreased the urea levels by treatment of flowers fraction (AFL+CPA), and increased the cholesterol and ALT activity by the treatment of leaves fraction (AFO+CPA). The ethyl acetate fraction, especially the leaves had a higher hepatotoxic effect, although it led to a protective effect in animals and to DNA damage induced by CPA. The group treated only with C. peltophoroides showed no mutagenic potential when compared to the negative control group. This study points the antimutagenic effect of ethyl acetate fraction of leaves, which demonstrates the need for further studies in order to elucidate its chemical structures involved.